2014
DOI: 10.1115/1.4026001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wall Temperature on Turbine Blade Tip Aerothermal Performance

Abstract: Currently the aerodynamics and heat transfer over a turbine blade tip tend to be analyzed separately with the assumption that the wall thermal boundary conditions do not affect the over-tip-leakage (OTL) flow field. There are some existing correlations for correcting the wall temperature effect on heat transfer when scaled to engine realistic conditions. But they were either developed to account for the temperature dependence of fluid properties largely empirically, or based on a boundary-layer model. It would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Such non-linear behavior has also been recently reported in the previous CFD analysis by Zhang et al 2014and Maffulli and He 2014. The experimental evidence obtained in the present study confirmed their previous numerical analysis and findings.…”
Section: Tr Effect On Small Tip Gapssupporting
confidence: 92%
See 1 more Smart Citation
“…Such non-linear behavior has also been recently reported in the previous CFD analysis by Zhang et al 2014and Maffulli and He 2014. The experimental evidence obtained in the present study confirmed their previous numerical analysis and findings.…”
Section: Tr Effect On Small Tip Gapssupporting
confidence: 92%
“…The TR effect on tip aerothermal performance has been addressed numerically by some recent CFD studies. Zhang et al (2014) found that the wall-gas temperature ratio could greatly affect the transonic OTL flow field, and there is a strong two-way coupling between aerodynamics and heat transfer. The feedbacks of the thermal boundary condition to aerodynamics behave differently at different flow regimes over the tip, clearly indicating a highly localized dependence of the HTC upon wall temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Within the figure, color variations denote tip surface heat flux variations, and greyscale variations denote flow density gradient distributions which were employed in these studies utilized squealer configurations [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], partial squealer configurations [61,64,69], and winglet configurations [73,74]. Smooth blade tips were employed by Thorpe et al [75], Green et al [59], Key and Arts [62], O'Dowd et al [76,77], Wheeler et al [78], Zhang et al [55,56], Shyam et al [79], Atkins et al [80], Wheeler and Saleh [70], Anto et al [81], Virdi et al [68], Wheeler and Sandberg [82], Li et al [65], Zhang et al [83], Zhang and He [84], Wang et al [69], Zhou [71], Jung et al [61], Gao et al [85], and Kim et al [64]. Most of these investigations (which involved experimental measurements) employed annular or linear cascades with stationary blades.…”
Section: Interactions Which Included Thermal Transport and Convectivementioning
confidence: 99%
“…The resulting adiabatic wall temperature, T * ad =540.5 K, is in the range of typical turbine rotor applications. The ratio of the wall temperature to the adiabatic wall temperature T * w /T * ad =0.7 is chosen to mimic realistic aero-engine conditions (Zhang & He 2014), where blade cooling is most often applied to avoid excessive surface temperature. The resulting non-dimensional wall temperature is T w =0.75.…”
Section: Turbomachinery Applicationsmentioning
confidence: 99%